2012
DOI: 10.1038/ncomms1671
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of anterior–posterior axis formation in the developing mouse embryo

Abstract: The development of an anterior–posterior (AP) polarity is a crucial process that in the mouse has been very difficult to analyse, because it takes place as the embryo implants within the mother. To overcome this obstacle, we have established an in-vitro culture system that allows us to follow the step-wise development of anterior visceral endoderm (AVE), critical for establishing AP polarity. Here we use this system to show that the AVE originates in the implanting blastocyst, but that additional cells subsequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
87
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(92 citation statements)
references
References 33 publications
3
87
0
2
Order By: Relevance
“…Self-assembly/ organization has also been observed directly in attached mammalian blastocysts in vitro. These studies established that human (Deglincerti et al, 2016a;Shahbazi et al, 2016) and mouse (Bedzhov et al, 2014b;Morris et al, 2012) embryos can be cultured ex vivo in the absence of maternal tissues, showing important selforganizing events. Although these assays are currently ethically limited to studying human embryos for only up to 14 days of development, they provide a complementary approach to embryoid and gastruloid experiments for quantitatively studying early human development and are likely to become increasingly popular in the coming years.…”
Section: Introductionmentioning
confidence: 99%
“…Self-assembly/ organization has also been observed directly in attached mammalian blastocysts in vitro. These studies established that human (Deglincerti et al, 2016a;Shahbazi et al, 2016) and mouse (Bedzhov et al, 2014b;Morris et al, 2012) embryos can be cultured ex vivo in the absence of maternal tissues, showing important selforganizing events. Although these assays are currently ethically limited to studying human embryos for only up to 14 days of development, they provide a complementary approach to embryoid and gastruloid experiments for quantitatively studying early human development and are likely to become increasingly popular in the coming years.…”
Section: Introductionmentioning
confidence: 99%
“…Collective AVE migration is complex and involves highly coordinated protrusive activity, cell translocation, cell division, and intercalation during a period of embryo growth and global cell movements (Srinivas et al 2004;Migeotte et al 2010;Takaoka et al 2011;Trichas et al 2011Trichas et al , 2012Morris et al 2012). To analyze AVE migration in more detail, we used high-resolution confocal video microscopy on live embryos expressing two transgenes: the AVE cell marker Hex-GFP and a ubiquitous membrane marker, GFP-GPI (Srinivas et al 2004;Rhee et al 2006).…”
Section: Cellular Mechanisms Of Ave Collective Migrationmentioning
confidence: 99%
“…Previous studies had reported that DVE cells at the migration front are required to initiate DVE movement, therefore acting as a leading population (Morris et al, 2012;Takaoka et al, 2011). Their displacement involves intercalation and production of long and stable basal projections (Migeotte et al, 2010;Srinivas et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, upon reaching the proximity of the Emb/Xemb border, non-leading DVE cells extend very long projections that appear to contact the first or second cell rows of the migration front. It is tempting to speculate that distally located Emb VE cells need to make contact with the subpopulation of leading DVE cells, which is characterised by a distinct origin and specific expression of the markers Cer1 and Lefty1 (Morris et al, 2012;Takaoka et al, 2011), in order to receive the signals that regulate their migration and/or arrest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation